Peningkatan Aktivitas dan Hasil Pelajaran Matematika Kompetensi Dasar Sistem Koordinat Kartesius dengan Menggunakan Metode Diskusi Kelompok pada Siswa Kelas VIII A Semester I SMP Negeri 2 Ampelgading Tahun Pelajaran 2022/2023 - Sukardi, Sukardi (Universitas PGRI Semarang, 2023)
The problem faced is that student learning outcomes regarding the Cartesian coordinate system are still low, and student learning activities are not good for class VIII A students at SMP Negeri 2 Ampelgading semester I of the 2022/2023 academic year. This PTK is carried out in two cycles, each cycle has 4 stages: planning, action, observation and reflection. The results of classroom action research show an increase in learning outcomes. This is proven by the average pre-cycle test result of 63.59, 37.50% completeness, the average first cycle result of 68.91, 72.50% completeness, increasing to 81.56 with 93.75% completeness in cycle II.